SISTEM PERMOHONAN INSTRUMENTASI KALIBRASI DAN BUKU TAMU DIGITAL BMKG WILAYAH III - Theresia Angel Oktarina Pasaribu; Luh Gede Astuti; Anak Agung Istri Ngurah Eka Karyawati (Jurnal Pengabdian Informatika, 2026)
ABSTRACTBMKG Region III Denpasar is an institution that provides public services such as equipment calibrationrequests and guest registration. However, these processes are still carried out manually using various platformslike Zoho Forms, Google Drive, and WhatsApp, leading to inefficiencies, a high risk of errors, and difficultiesin data tracking. This study aims to develop a web-based calibration request and digital guest book system toimprove the efficiency, accuracy, and transparency of services. The system is designed using MySQL for thedatabase, HTML, CSS, Bootstrap, and JavaScript for the interface, and PHP for server-side logic. Theimplementation results show that the system can automate the processes of request submission, paymentvalidation, complaint management, and guest registration in an integrated manner. Therefore, this systemsignificantly contributes to the digitalization of public services at BMKG Region III.Keywords: BMKG, Inskal Request System, Digital Guest Book, Public Services, Website, Service Automation